Brain‐Cortex Microglia‐Derived Exosomes: Nanoparticles for Glioma Therapy. Issue 10 (19th February 2018) - Murgoci, Adriana‐Natalia; Cizkova, Dasa; Majerova, Petra; Petrovova, Eva; Medvecky, Lubomir; Fournier, Isabelle; Salzet, Michel
Abstract: The function and integrity of the nervous system require interactive exchanges among neurons and glial cells. Exosomes and other extracellular vesicles (EVs) are emerging as a key mediator of intercellular communication, capable of transferring nucleic acids, proteins and lipids influencing numerous functional and pathological aspects of both donor and recipient cells. The immune response mediated by microglia‐derived exosomes is most prominently involved in the spread of neuroinflammation, neurodegenerative disorders, and brain cancer. Therefore, in the present study we describe a reproducible and highly efficient method for yielding purified primary microglia cells, followed by exosome isolation and their characterization. An in vitro biological assay demonstrates that microglia‐derived exosomes tested on a 3D spheroid glioma culture were able to inhibit tumor invasion in time course. These results evidence that brain microglia‐derived exosomes could be used as nanotherapeutic agents against glioma cells. Abstract : Nanotherapeutic agents : A reproducible and highly efficient method for yielding purified primary microglia cells is presented. The results demonstrate that microglia‐derived exosomes, tested on a 3D spheroid glioma culture, are able to inhibit tumor invasion, showing that these could be used as nanotherapeutic agents against glioma cells.